Factors Related to Prospective Labor Selection by Pregnant Mother in Tosiba Primary Health Care, Kolaka District - Yuhanah Yuhanah (Sorume Health Sciences Journal, 2020)
The use of birth assistance in Indonesia by midwives in the community is still low (77.03%) if compared to the target indicator of delivery must be 95% by Nakes. This study aims to determine the factors associated with the selection of labor assistants by pregnant women in Tosiba Health Center, Samaturu District, Kolaka Regency in 2017. The research variables consisted of socio-economic status, culture and distance of health facilities. Form of Analytical research with Cross Sectional Study. The number of samples is 84 respondents, using accidental sampling technique. Results of data analysis 70.2% of pregnant women chose birth attendants to health workers and 29.8% of pregnant women chose birth attendants to non-health workers. The chi-square test results have a socio-economic relationship but not significant (x2 = 5.403; P = 0.024) and there is a Cultural relationship but not significant (x2 = 5.581; P = 0.024), while the distance of health facilities has a significant relationship (x2 = 9.188; P = 0.004). A new strategy related to the importance of delivery by Nakes in Pasyankes is very much needed through health sector programs involving cross-sectors including the implementation of continuous education to realize quality health degrees in accelerating the reduction of maternal and infant mortality, NAWACITA 2015-2019.